Ex-vivo modulation of spontaneous uterine contractility by some sodium ion channel blockers - Evi, Bafor Enitome; Adekunle , Idowu Florence; Osemelomen, Omoruyi; Okosun , Isibhakhomhen Victoria; Iduojemu, Ozolua Raymond (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Local anaesthetics of the amide class which act by sodium ion (Na+) channel blockade had been reported to stimulate uterine contractility rather than cause inhibition. This study therefore sets out to investigate the effect of selected Na+ channel blockers that do not belong to the class of local anaesthetics, on uterine contractility. This was necessary in order to ascertain if the effect previously observed with the amide anaesthetics were a function of the class of anaesthetics, a function of Na+ channel blockade or other interactions. Three Na+ channel blocking drugs and one amide anaesthetic drug were used for the investigation. These included: lidocaine (0.0002 - 2.222 ?g/ml), quinine (0.003 - 1.332 ?g/ml), chloroquine (0.64 -710 ng/ml) and phenytoin (0.001 - 1.11 ?g/ml). These drugs were added cumulatively to the isolated mouse uterus which was mounted in a 10 ml organ bath filled with continuously aerated physiological solution and set at a temperature of 37ºC. The effect of these drugs on the amplitude and frequency of spontaneous uterine contractions were determined. Lidocaine, quinine and chloroquine were observed to concentration-dependently increase the amplitude and frequency of uterine spontaneous contractions (p < 0.05). However, phenytoin was observed to decrease both the amplitude and frequency of uterine spontaneous contractions (p < 0.05). The stimulation contradicts the effect of Na+-channel blockade on smooth muscle contractility and therefore suggests other mechanism(s) of activity apart from Na+-channel blockade or a new role for Na+-channel blockade on uterine smooth muscles. This study has shown that besides the amide anaesthetics, other Na+-channel blocking drugs produce stimulation of uterine contractility.